3D characterization of microbially induced carbonate precipitation in rock fracture and the resulted permeability reduction - Wu, Chuangzhou (2021)
A new seepage control method for fractured rock is biogrouting through a microbially induced calcite precipitation (MICP) process. A study on the spatial distribution of biogrout in a rock fracture and its effect on permeability reduction is presented in this paper. A series of experiments together with 3D scanning and 3D flow simulation were performed on rock fractures with various initial apertures treated by bio-grouting. A lognormal distribution of MICP precipitates along the flow direction in a fracture was observed. The 3D flow simulation of biogrouted fracture has revealed that the routinely adopted parallel plate model (cubic law) for estimating permeability of channel flow is no longer applicable when the fracture aperture is less than the critical value of 0.7 mm based on this study. This is because partially clogging will occur when the fracture aperture is less than the critical value, resulting in a transition of the flow type from surface flow to channel flow. A semi-empirical equation which can account for the effect of flow type has been proposed for estimating the permeability reduction due to bio-grouting for rock fractures.